Sistem Pakar Diagnosa Penyakit Pada Ayam Menggunakan Metode Forward Chaining: (Studi Kasus: Dinas Peternakan Dan Kesehatan Hewan Kabupaten Asahan) - M Wahyu Suranta; Angga Pratama; Himmatur Rija (Jurnal Tika, 2024)
Asahan Regency is one of the areas with a poultry population of laying hens with a population of 4,725,195 and broiler with a population of 27,881,073 which will continue to increase where the accompanying diseases are also increasingly complex. Diseases in chickens that occur in Asahan District will of course greatly affect chicken production in Asahan District. Therefore, it is necessary to develop an expert system where the system is a reference whether the chickens kept are infected with the disease or not, and if infected it is hoped that the disease suffered by the chickens being kept can be identified quickly and can carry out appropriate treatment. So that intensive care and maintenance of chickens will generate multiple profits. In this study a system was built by applying the Forward Chaining method to get the results that are closest to the symptoms of the disease that attacks these animals